Association between prolonged exposure to long working hours and stroke subtypes in the CONSTANCES cohort. Issue 4 (23rd February 2023) - Fadel, Marc; Sembajwe, Grace; Li, Jian; Leclerc, Annette; Pico, Fernando; Schnitzler, Alexis; Roquelaure, Yves; Descatha, Alexis
Abstract : Background: Though there is increasing evidence on the effect of long working hours (LWH) and stroke, few studies have distinguished stroke subtypes. We examined the associations between LWH and ischaemic or haemorrhagic stroke after adjusting for cardiovascular risk factors. Methods: From a national population-based cohort CONSTANCES, baseline questionnaires and initial health examinations were used to retrieve sociodemographic and cardiovascular risk factors from 2012 to 2018. LWH were defined as self-reported working time≥10 hours daily for at least 50 days per year. Incident cases of stroke were collected using International Classification of Disease codes recorded in the National Health Data System. Associations between LWH and stroke were investigated using multinomial models adjusted for cardiovascular risk factors. Results: Among the 160 751 participants who were free from stroke at baseline, exposure to LWH≥10 years was reported by 20 723 participants, and 190 incident cases of stroke were identified, including 134 ischaemic and 56 haemorrhagic. Exposure to LWH was associated with an elevated odds of ischaemic stroke (OR=1.61 (1.04–2.49)) and haemorrhagic stroke (OR=2.50 (1.38–4.53)) in unadjusted models. In adjusted multivariable models, only the LWH association with haemorrhagic stroke remained significant (aOR=1.92 (1.01–3.09)). Conclusions: LWH were associated with stroke, though it remained significant for haemorrhagic stroke only after adjustments. Differences in direct and indirect biological pathways and lack of power in the ischaemic subgroup may explain these results and further studies on the impact of mediating and effect measure modifying factors are needed. Nevertheless, policies that attenuate effects of both LWH and cardiovascular risks factor are warranted.